Australian Fires 2019–2020: Tropospheric and Stratospheric Pollution Throughout the Whole Fire Season - Kloss, Corinna; Sellitto, Pasquale; von Hobe, Marc; Berthet, Gwenaël; Smale, Dan; Krysztofiak, Gisèle; Xue, Chaoyang; Qiu, Chenxi; Jégou, Fabrice; Ouerghemmi, Inès; Legras, Bernard (Frontiers in Environmental Science, 2021)
The historically large and severe wildfires in Australia from September 2019 to March 2020 are known to have injected a smoke plume into the stratosphere around New Year, due to pyro-cumulonimbus (pyro-Cb) activity, that was subsequently distributed throughout the Southern Hemisphere (SH). We show with satellite, ground based remote sensing, and in situ observations that the fires before New Year, had already a substantial impact on the SH atmosphere, starting as early as September 2019, with subsequent long-range transport of trace gas plumes in the upper-troposphere. Airborne in situ measurements above Southern Argentina in November 2019 show elevated CO mixing ratios at an altitude of 11 km and can be traced back using FLEXPART trajectories to the Australian fires in mid-November 2019. Ground based solar-FTS (Fourier Transform Spectroscopy) observations of biomass burning tracers CO, HCN and C2H6 at Lauder, South Island, New Zealand show significantly enhanced tropospheric columns compared to previous years, with enhancements already starting in September 2019 and then increased enhancements in January 2020. For HCN stratospheric mixing ratios increased significantly between September and mid-December 2019. With averaged satellite observations and still increased aerosol values following the Ulawun eruption in 2019, we observe no clear stratospheric and upper-tropospheric aerosol enhancements from the Australian fires, before the pyro-Cb events at the end of December 2019. However, with the clear enhancement of fire tracers, we suggest the period September to December 2019 (prior to the major pyro-Cb events) should be taken into account in terms of fire pollutant emissions when studying the impact of the Australian fires on the SH atmosphere.